Therapeutic applications of stem cells from human exfoliated deciduous teeth: a review - Baweja, Mani (International Journal of Research in Medical Sciences, 2020)
Dental stem cells have been found to have the ability to differentiate into nerve cells, adipose cells, chondrocytes, osteoblasts, myocytes, hepatocytes, and odontoblasts. They can be derived from permanent teeth or deciduous teeth. Stem cells from human exfoliated deciduous teeth (SHED) have a higher proliferation rate and higher osteogenic and neurogenic potential than dental pulp stem cells (DPSC). Therefore, SHEDs are an attractive cell source for tissue regeneration. A large plethora of in vitro and animal studies have been conducted in the last few decades that has demonstrated the potential uses of these cells for the treatment of oral and non-oral diseases. The aim of this article was to review the potential therapeutic applications of stem cells derived from human exfoliated deciduous teeth. A Medline search was done, including international literature, published in English between 2003 and 2020. In this area, further research is needed to ensure the applicability of SHED in the treatment of diseases in humans.